Strengthening of Position The Regional Representative Council (DPD) in the Indonesian Constitutional System - Irsyada, Nadia Elza; Wardana, Dodi Jaya (Universitas Semarang, 2024)
This article aims to discuss the strengthening of the position of The Regional Representative Council (DPD) In the Indonesian constitutional system, as a representative institution region. The Regional Representative Council (DPD) is a high state institution that was formed through amendments to the 1945 Constitution of the Republic of Indonesia (UUD 1945). The aim is to strengthen regional representation in decision-making at the national level. Even though it is expected to be able to fight for regional interests and act as a balancer to central power, the DPD is often considered to have limited authority compared to the People's Representative Council (DPR). This research uses a normative juridical method, which focuses on the analysis of statutory regulations and legal documents related to the position and authority of the DPD. This method is used to understand the legal provisions governing the DPD through a review of the 1945 Constitution, related laws, and relevant legal literature. After the amendment to the 1945 Constitution, Indonesia's constitutional structure underwent significant changes, including the formation of the DPD as a regional representative institution. Although the DPD has the authority to provide consideration to draft laws relating to regional interests, its role is often considered less influential than that of the DPR. These limitations, for example in the formal review of Law Number 17 of 2023 concerning Health, reflect the challenges in implementing the DPD's role and the existence of legal politics that leads to decentralization. The evaluation shows that although the DPD is designed to strengthen regional autonomy, implementing functions and coordination between the DPD, DPR, and the central government still face obstacles.